UJI DAYA HASIL DAN MUTU BENIH BEBERAPA KULTIVAR SORGUM (Sorghum bicolor L.) DENGAN JARAK TANAM YANG BERBEDA - Supriono Supriono; Elza Zuhry; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of this research was to determine the yield and seed quality of four sorghum cultivars at different plant spacing and find out proper plant spacing for each sorghum cultivars. This research was conducted at the Agriculture experiment station and in the plant breeding laboratory, Riau University from April 2015 to Agustus 2015. Research conducted an experiment using a randomized block design (RBD), which consists of two factors, the first factor is a cultivar of sorghum which consists of cultivars Patir 9, Patir 10, Pahat and Mandau, the second factor is the spacing of which is comprised of a spacing of 75 cm x 15 cm, 75 cm x 20 cm and 75 cm x 25 cm, in order to obtain 12 test combinations and repeated 3 times so that there are 36 experimental units. Observational data were analyzed statistically using analysis of variance and continued with further test Tukey. The parameters were observed among panicle length, seed weight per panicle, seed weight per m2, weight of 1000 seeds, harvest moisture, test first count, germination test, speed test germination, plumula length, radicle length.The results showed that sorghum cultivars with a spacing of 75 cm x 15 cm tends to give the highest yield in cultivars Patir 9 (4.19 ton / ha), Mandau (4.01 ton/ ha), Pahat (3.58 ton/ ha) and Patir 10 (3,19 ton / ha). Cultivars Patir 9 and Mandau with a spacing of 75 cm x 15 cm have a higher yield potential than the two other cultivars tested. Plant spacing did not affect seed quality on all cultivars tested. Keywords: sorghum cultivars, plant spacing, yield and seed quality